Development of Student Worksheets on Biodiversity into Problem-Based Learning Integrated Local Wisdom Assisted Augmented Reality to Improve Students' Conservation Literacy - Iwan; Jeni; Nurfathurrahmah (Florea : Jurnal Biologi dan Pembelajarannya, 2026)
The low level of students’ conservation literacy in understanding and applying biodiversity concepts indicates the need for instructional innovation through the development of student worksheets based on Problem-Based Learning, integrated with local wisdom and supported by Augmented Reality media, to create more contextual, interactive, and meaningful learning experiences. The purpose of this study was to develop student worksheets on biodiversity materials oriented towards problem-based learning integrated with local wisdom and supported by augmented reality media to improve students' conservation literacy. The research method refers to ADDIE research and development. The subjects of this study were 23 students of SMA YABT Manokwari. The data collection instruments were validation sheets and questionnaires to determine  validity students' responses to the student worksheets and the provision of student conservation literacy test questions. The data analysis was carried out descriptively by calculating validation results nalyzing student response questionnaires and student conservation literacy. The findings of this study, the media and material expert validation test obtained 94.44% (very valid) and he validation of conservation literacy questions obtained 96.82% (very valid). Practicality was rated 86.09% (very practical). The average value of students' conservation literacy was 70.05 indicating that students' conservation literacy values ​​were in the good range. The Study concludes The conclusion of the study is that the worksheets for biodiversity oriented to problem-based learning integrated with local wisdom and assisted by Augmented Reality improve students' conservation literacy.